Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 11 - Rational Expressions and Functions - 11-4 Adding and Subtracting Rational Expressions - Mixed Review - Page 677: 61



Work Step by Step

Simplifying the question, $\frac{(y^{4}-y^{2})}{y^2-2y-3}$ Factorising the numerator, =$\frac{(y^{4}-y^{2})}{y^2-2y-3}$ = $\frac{y^{2}(y^{2}-1)}{y^2-2y-3}$ = $\frac{y^{2}(y-1)(y+1)}{y^2-2y-3}$ Factorising the denominator, =$\frac{y^{2}(y-1)(y+1)}{y^2-2y-3}$=$\frac{y^{2}(y-1)(y+1)}{y^2-3y+y-3}$ =$\frac{y^{2}(y-1)(y+1)}{y(y-3)+1(y-3)}$ =$\frac{y^{2}(y-1)(y+1)}{(y+1)(y-3)}$ Cancel the common terms, =$\frac{y^{2}(y-1)}{(y-3)}$ This is the answer.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.